Confidentiality and Integrity of the Biometric Fingerprint Template Protection - Ghazali, Taqiyah Khadijah; Zakaria, Nur Haryani (International Journal of Engineering and Technology, 2018)
Fingerprint is one of the most reliable biometric-based authentication methods for personal identification and providing access control to many applications. Due to its accuracy and convenience, it can never be forgotten or lost since biometric characteristics are biological parts of the users itself. However, previous studies have shown that, fingerprint template are exposed to threat in which the attackers can steal and modified the template to acquire illegal entree. Therefore, a technique to protect the biometric template is required. Biometric template protection consists of two categories, which are feature transformation and biometric cryptosystem. Thus, this paper will focus on biometric cryptosystem specialize in the key binding scheme, which is fuzzy commitment technique. In the key binding scheme, the helper data must not reveal any information concerning the biometric data, but previous studies have shown that it does certainly leak some crucial information. Hence, this paper intends to propose an enhancement to the existing fuzzy commitment technique. The enhancement will involve the key binding scheme of secret key with biometric template to generate AES-128 key algorithm, which is to provide confidentiality alongside with the Offset Codebook Mode (OCB), an authenticated encryption (AE) mode to provide integrity. The enhancement is expected to improve the technique, which will be more secure and robust while maintaining the existing performance.